Third culture kids : growing up among worlds - Pollock, David C.; Van Reken, Ruth E., 1945- (Boston : Nicholas Brealey Pub., 2009)
"For nearly a decade, Third Culture Kids: The Experience of Growing Up Among Worlds has been the authority on the experiences of 'third culture kids'--children who grow up or spend a significant part of their childhood living abroad. Early on, TCKs were identified as the prototype 'citizen of the future.' That time is now, as more and more children are growing up among worlds, creating a culturally rich and diverse world. This expanded edition profiles the personal challenges that third culture kids experience, from feelings of rootlessness and unresolved grief to struggles with maturity and identity. It also profiles the benefits of the unique third culture lifestyle, producing extraordinary people with well-rounded skill sets. Highlighting dramatic changes brought about by instant communication and new mobility patterns, the new edition shows how the TCK experience is becoming increasingly common and valuable. The authors also introduces 'CCKs' cross-cultural kids, children of biracial or bicultural parents, immigrants and international adoptees--all of this bringing hidden diversity to our world and challenging our old notions of identity and 'home'."--Publisher's description.
Where is home? : Erika's story -- Who are "third culture kids"? -- Who are "cross-cultural kids? -- Why a cross-cultural childhood matters -- Why high mobility matters -- Benefits and challenges -- Personal characteristics -- Practical skills -- Rootlessness and restlessness -- Relational patterns -- Developmental issues -- Unresolved grief -- Building a strong foundation -- Dealing with transition -- Meeting educational needs -- Enjoying the journey -- Coming "home" : reentry -- How sponsoring organizations can help -- It's never too late.
Includes bibliographical references and index.
Keywords: Social interaction in children -- Foreign countries; Social skills in children -- Foreign countries; Children -- Travel -- Foreign countries; Children -- Foreign countries -- Attitudes; Intercultural communication -- Foreign countries; Parents -- Employment -- Foreign countries; Third-culture children